Distribuição geográfica da tesoura-do-brejo (Gubernetes yetapa): uma abordagem multiescala - Wagener, Thuani Luísa Saldanha (2025)
The Streamer-tailed Tyrant (Gubernetes yetapa) is a wetland-associated bird whose biology and distribution remain poorly understood. This study represents the first investigation of the species’ spatial and temporal distribution patterns, encompassing historical factors as well as future projections under climate change scenarios. We also explored potential seasonal movements and environmental variables influencing its occurrence across multiple spatial scales. To achieve this, we compiled occurrence records from citizen and open science databases, complemented by field surveys conducted in 66 wetland areas within the Pampa biome, collecting presence-absence data and landscape characteristics. These data were integrated with bioclimatic variables (current and future), topographic features, and land-use change data from 1985 to 2023. We employed different methodological approaches, including Ecological Niche Models and occupancy models accounting for imperfect detection. We also applied Generalized Linear Models to assess the variables affecting occurrence probability, and used the Kolmogorov-Smirnov test to compare latitude, longitude, elevation, wetness, and topographic position across seasons. Our models indicate that climate change may drastically reduce suitable areas for G. yetapa, with contractions in G. yetapa’s range by 2100, especially outside central and southeastern Brazil. Although some regions may gain suitable areas, the low coverage of wetlands within protected areas renders such gains insufficient to ensure long-term species survival. Considering potential seasonal movements, we found no evidence of largescale migration. However, we observed seasonal differences in variables such as longitude, elevation, and topographic wetness index. The number of records also differed between the breeding and non-breeding periods, suggesting potential regional-scale shifts. In the state of Rio Grande do Sul, occupancy models revealed a strong dependence on open wetlands with flat terrain and the co-occurrence of other wetland-associated birds. At a local scale, the presence of G. yetapa is associated with shrubby wetlands containing vegetation between one and two meters in height, and landscapes covered by grasslands and wetlands. Nevertheless, we identified a 65.75% loss of wetlands in these areas since 1985, accompanied by a 14.75% increase in forest cover. We conclude that G. yetapa faces multiple threats at all spatial scales analyzed, with habitat loss and degradation of wetland environments being the most critical. We recommend continuous monitoring of the species, especially in Rio Grande do Sul, and a new evaluation of its conservation status. Despite being considered locally common due to its detectability, our findings highlight major distributional gaps likely driven by habitat scarcity. This study represents an essential first step toward understanding the ecology and conservation needs of wetland-associated birds and emphasizes the urgent need to protect these increasingly neglected ecosystems.